International Muslim Students: Challenges and Practical Suggestions to Accommodate Their Needs on Campus - Chen, Bateer; Tabassum, Humaira; Saeed, Muhammad Aamir (Journal of International Students, 2019)
In recent years there has been an increase in the enrollment of Muslim international students in higher education institutions in China. This research provides a brief overview of the issues that international Muslim students face during their campus life, such as adopting a new culture, lack of understanding from the broader university community, poor cultural or religious-responsive education, lack of accommodation for religious practices, and social isolation. This qualitative study also highlights some information about the unique needs of the Muslim students on campus and identifies areas for improvement. To overcome these issues, specific practical suggestions are given to the university administration, faculty, and staff to meet the needs of Muslim students, not only academically, but also socially and culturally.